2021
DOI: 10.2147/idr.s290434
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of β-Lactamase Genes and Genetic Context of blaKPC-2 in Clinical Carbapenemase-Producing Klebsiella pneumoniae Isolates

Abstract: Background This study was designed to characterize the dissemination mechanism and genetic context of Klebsiella pneumoniae carbapenemase (KPC) genes in carbapenem-resistant Klebsiella pneumoniae (CRKP) isolates. Methods A retrospective analysis was performed on CRKP strains isolated from a teaching hospital of Wenzhou Medical University during 2015–2017. Polymerase chain reaction (PCR)-based amplification and whole-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Sequencing analysis showed that in addition to the bla KPC-2 gene, one or more other kinds of β-lactamase genes (such as bla CTX-M , bla SHV , and bla TEM ) were identified in these KPC-producing K. pneumoniae strains, with 53% (8/15) of the strains carrying the ESBL gene, bla CTX-M ; this is consistent with previous reports. 23 Consistent with other studies, the isolates were also more resistant to quinolones and trimethoprim/sulfamethoxazole. Quite often, plasmids carrying ESBL genes also carry other drug-resistant genes including quinolone and trimethoprim/sulfamethoxazole resistance genes.…”
Section: Discussionsupporting
confidence: 90%
“…Sequencing analysis showed that in addition to the bla KPC-2 gene, one or more other kinds of β-lactamase genes (such as bla CTX-M , bla SHV , and bla TEM ) were identified in these KPC-producing K. pneumoniae strains, with 53% (8/15) of the strains carrying the ESBL gene, bla CTX-M ; this is consistent with previous reports. 23 Consistent with other studies, the isolates were also more resistant to quinolones and trimethoprim/sulfamethoxazole. Quite often, plasmids carrying ESBL genes also carry other drug-resistant genes including quinolone and trimethoprim/sulfamethoxazole resistance genes.…”
Section: Discussionsupporting
confidence: 90%
“…MLST analysis showed that the K. pneumoniae strain KP32558 was assigned to ST656, a rare ST type and firstly reported in China in 2012 ( Wang et al., 2012 ). The frequently detected carbapenemase in these bacteria was KPC-2 ( Liu et al., 2021 ) and NDM-1 ( Li et al., 2020 ). Our study represents the first report of the emergence of NDM-5 and MCR in ST656 K. pneumoniae clinical isolate.…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition of conjugant resistance also showed that drug resistance was transferable. bla TEM is often part of the genetic environment of bla KPC-2 ( Liu et al., 2021 ; Zhai et al., 2021 ), so both genes were transferred within the plasmid. In Europe and the United States, transposon Tn 4401 is the most common gene element carrying bla KPC ( Naas et al., 2008 ; Wang et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%